CLINICAL AND IMAGING CHARACTERISTICS AND SELECTED ASSOCIATED FACTORS IN PATIENTS WITH LUMBAR INTERVERTEBRAL DISC HERNIATION UNDERGOING SURGERY AT NHAN DAN 115 HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe clinical characteristics and analyze the association between clinical symptoms and magnetic resonance imaging features in patients with lumbar disc herniation undergoing surgery at People’s Hospital 115 in 2025.Materials and Methods: A descriptive study was conducted on 123 surgically treated patients with lumbar disc herniation. Data collected included general characteristics; clinical symptoms (radiating leg pain, numbness/paresthesia, lower-limb weakness); and magnetic resonance imaging findings (axial herniation zone, nerve root compression grade, and herniation morphology). Associations were analyzed using the Chi-square test or Fisher’s exact test; p0.1). Herniation morphology (bulge/protrusion vs extrusion/sequestration) was not significantly associated with symptom duration (p=0.508).Conclusion: Among surgically treated patients with lumbar disc herniation, the predominant clinical presentation was radicular pain and low back pain. Nerve root compression severity on magnetic resonance imaging was associated with numbness/paresthesia, whereas the axial herniation zone alone did not clearly predict major symptoms. Magnetic resonance imaging should be integrated with standardized neurological examination and comprehensive clinical assessment to guide diagnosis and treatment.
Keywords: Lumbar disc herniation; clinical characteristics; magnetic resonance imaging; nerve root compression.